The first successful application of Optically Stimulated Luminescence dating to a colonial era (<0.25 ka) archaeological site in Australia. (April 2019) - Williams, Alan N.; Toms, Phil S.; Marcus, David; Yousif, Anita; McGuinness, James; O'Sullivan, Ashley; Barry, Laressa; Bryant, Tessa; Wood, Jamie C.
Abstract: While exploration of Australian post-colonial (≤0.25 ka) OSL dating is well established in a range of natural sedimentary contexts (e.g. fluvial, aeolian, coastal), to date there have been no successful examples of the technique applied to archaeological sediments of this era. Here we present the results of multi-phase compliance-based archaeological excavations of a new bridge crossing, the Hawkesbury-Nepean River (northwest Sydney). These works identified a Last Glacial Maximum (LGM) aeolian deposit through which a colonial era drainage system had been excavated. Historical documents reveal the construction of the system occurred between 1814 and 1816 CE. An opportunistic range-finding Optically Stimulated Luminescence (OSL) sample was obtained from anthropogenic trench backfill – composed of reworked LGM deposits – immediately above the drainage system. Minimum and Finite Mixture age models of single grain quartz OSL provided a date of 1826 CE (1806–1846 CE), in close agreement with the documented age of construction. These findings provide the first evidence of a colonial structure reliably dated using OSL, and demonstrate the feasibility of wider deployment of OSL dating to other archaeological sites of the recent era (≤0.25 ka). We propose that such environments associated with large volumes of sand-rich backfill, in particular, likely heighten OSL dating success. We propose that well-documented historical archaeological sites in Australia also have the potential to provide a robust testing ground for further evaluating the accuracy of OSL dating in a range of young archaeological sedimentary contexts, potentially to sub-decadal levels. Highlights: First successful application of OSL methods to a colonial-era anthropogenic backfill deposit Archaeological excavation uncovered a drainage system documented to 1814–16 CE. Dating of the drain backfill initially thought to be part of an LGM aeolian unit returned an age of 1826 (1806–46) CE. Reinforces the effectiveness and comparability of OSL with radiocarbon techniques in the colonial era Well documented colonial era sites may prove robust testing grounds to improve OSL methods.